2020
DOI: 10.3390/app10031088
|View full text |Cite
|
Sign up to set email alerts
|

Complete Benzene Oxidation over Mono and Bimetallic Pd—Au Catalysts on Alumina-Supported Y-Doped Ceria

Abstract: The protection of environment and human health stimulates intensive research for abatement of volatile organic compounds (VOCs) in the atmosphere. Complete catalytic oxidation is an efficient, environmentally friendly and economically feasible method for elimination of VOCs. This study aims to design high performing and cost-effective catalytic formulations by exploration of appropriate and economically viable supports. Alumina-supported ceria (30 wt.%) and Y2O3 (1 wt.%)-doped ceria were prepared by mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…The observed temperature for 100% complete benzene oxidation over Pt FANaX is higher than this of Pt/Al 2 O 3 catalysts [51], and it is compatible with this of Au and Pd catalysts loaded on iron modified cerium oxides [52,53] and Mn/Co binary catalysts [54] and cobalt-cerium oxides [55]. The advantages are the utilization of fly ash from one side and a cheap source for the preparation of zeolite support from the other side.…”
Section: Resultssupporting
confidence: 66%
“…The observed temperature for 100% complete benzene oxidation over Pt FANaX is higher than this of Pt/Al 2 O 3 catalysts [51], and it is compatible with this of Au and Pd catalysts loaded on iron modified cerium oxides [52,53] and Mn/Co binary catalysts [54] and cobalt-cerium oxides [55]. The advantages are the utilization of fly ash from one side and a cheap source for the preparation of zeolite support from the other side.…”
Section: Resultssupporting
confidence: 66%
“…213 Tabakova et al reported a bimetallic Pd–Au catalyst using alumina-supported Y-doped ceria as support for complete benzene oxidation. 214 They found that the interaction between the Au particles and ceria leads to the enhanced oxygen vacancy creation ability, which benefits the activation of oxygen and benzene. The lattice oxygen from ceria surface layers could participate in the redox transfer of Pd 0 to PdO, accelerating hydrocarbon adsorption and transformation.…”
Section: Some Promising Applications Of Alumina-supported Pd-based Ca...mentioning
confidence: 99%
“…101,102 Li and co-workers reported CeO 2 supported Pd 1 −Au 1 (wt %) BMC for αalkylation of ketones with primary alcohols under visible light where unsaturated ketone formation takes place in the absence of visible light irradiation. 103 Furthermore, oxidation of benzyl alcohol (Table 1, entry 4−5,10), 30,19,20 glucose (Table 1, entry 20), 40 combustion of benzene 104,105 and propene, 106 hydrogenation of C−C double bond in α,β-unsaturated aldehyde, 107 α,β-unsaturation of cyclohexanones (Scheme 1), 108 and C−H functionalization of chalcones 109 111 and decomposition as well coupling of methane (CH 4 ) to liberate H 2 with hydrocarbons. 112 The zirconium oxide (ZrO 2 ) modified supported Pd−Au/γ-Al 2 O 3 catalyst also reflected its superiority for oxidation of benzyl alcohol (Table 1, entry 6) 26 and hydrosilylation of aryl chlorides.…”
Section: Types Of Catalytic Supports and Their Effects In Organic Tra...mentioning
confidence: 99%
“…After TiO 2 , ceria (CeO 2 ) is the most frequently applied metal support for Pd–Au BMCs preparation because of its affordability, accessibility, acid–base properties, and the ability to bind with a large variety of metals. , Li and co-workers reported CeO 2 supported Pd 1 –Au 1 (wt %) BMC for α-alkylation of ketones with primary alcohols under visible light where unsaturated ketone formation takes place in the absence of visible light irradiation . Furthermore, oxidation of benzyl alcohol (Table , entry 4–5,10), ,, glucose (Table , entry 20), combustion of benzene , and propene, hydrogenation of C–C double bond in α,β -unsaturated aldehyde, α,β -unsaturation of cyclohexanones (Scheme ), and C–H functionalization of chalcones also have been efficiently performed by CeO 2 supported Pd–Au BMCs. In addition, aluminum oxide (Al 2 O 3 ) supported Pd–Au BMCs also have been also developed and successfully applied for hydrogenation of butadiene (Table , entry 16), nitriles (Scheme b), diphenylacetylene (Table , entry 15), and decomposition as well coupling of methane (CH 4 ) to liberate H 2 with hydrocarbons .…”
Section: Types Of Catalytic Supports and Their Effects In Organic Tra...mentioning
confidence: 99%